2019
DOI: 10.1007/s11357-019-00127-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum beta-secretase 1 (BACE1) activity as candidate biomarker for late-onset Alzheimer’s disease

Abstract: Beta-secretase (BACE1) is a key enzyme in the formation of amyloid-β; its activity/ concentration is increased in brain and cerebrospinal fluid of patients with late-onset Alzheimer's disease (LOAD). Since BACE1 was found also in blood, we evaluated its potential as peripheral biomarker. To this aim, serum BACE1 activity was assessed in 115 subjects with LOAD and 151 controls. We found that BACE1 changed across groups (p < 0.001) with a 25% increase in LOAD versus controls. High levels of BACE1 (IV quartile) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 33 publications
4
43
0
Order By: Relevance
“…BACE1 has been recently found to be increased in the brain/CSF(cerebrospinal fluid) of patients with LOAD or mild cognitive impairment (MCI) 15,16 . BACE1 is present also in serum, as recently demonstrated by our group 17 and Shen et al 18 in two recent studies. In particular, we found that LOAD patients has significantly higher levels of serum BACE1 activity compared to controls, and this difference is independent of possible confounders including age, gender, and other risk factors for dementia 17 .…”
supporting
confidence: 71%
See 3 more Smart Citations
“…BACE1 has been recently found to be increased in the brain/CSF(cerebrospinal fluid) of patients with LOAD or mild cognitive impairment (MCI) 15,16 . BACE1 is present also in serum, as recently demonstrated by our group 17 and Shen et al 18 in two recent studies. In particular, we found that LOAD patients has significantly higher levels of serum BACE1 activity compared to controls, and this difference is independent of possible confounders including age, gender, and other risk factors for dementia 17 .…”
supporting
confidence: 71%
“…BACE1 is present also in serum, as recently demonstrated by our group 17 and Shen et al 18 in two recent studies. In particular, we found that LOAD patients has significantly higher levels of serum BACE1 activity compared to controls, and this difference is independent of possible confounders including age, gender, and other risk factors for dementia 17 . Based on this corollary of evidences, in the present study we investigated whether an increase in serum BACE1 activity is a specific feature of LOAD or might also characterize VAD.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Both BACE1 activity and protein concentrations in blood (mostly plasma but in some cases serum) are significantly increased in MCI individuals or patients with ADD compared to HC individuals, with a trend across different disease stages reflecting the direction of expression of the reported CSF biomarkers [34][35][36].…”
Section: Bace1 Biomarkers In Plasmamentioning
confidence: 99%